ASUHAN KEBIDANAN CONTINUITY OF CARE (COC) PADA NY. D DI KLINIK HAMIDAH NASUTION MEDAN - Minati Rahayu Syafitri; Kamelia Sinaga (LPPM STIKES Madani, 2023)
Abstract comprehensive midwifery care (continuity of care/COC) can optimize the detection of high maternal and neonatal risks. The aim of this care is to provide midwifery care for pregnant women, childbirth, postpartum, neonates and family planning at the Hamidah Nasution Clinic using a midwifery management approach. This type of research is a case study (case study). Guidelines for observation, interviews and documentation studies in the form of Midwifery Care starting from pregnancy, childbirth, postpartum, newborn and family planning. The results of the care given to Mrs. D 25 years old G1P0A0 starting from pregnancy, childbirth, postpartum, newborn and family planning. Runs smoothly and mother and baby are normal. Based on the results of the continuity of care midwifery care that had been carried out on Mrs. It is hoped that clients can apply the counseling that has been given during midwifery care so that the condition of the mother and baby remains good and can prevent complications and death. Keywords: Pregnancy, Maternity, Postpartum, Newborn, Family Planning